PID Control of Hydraulic Turbine with Excitation and Synchronization Systems - Ibrahim Jaber Alzubaydy, Ahmed; Dorohobid, Vadym; Borozdin, Mykola; Zakharchenko, Ruslan (International Journal of Engineering and Technology, 2018)
Hydroelectric energy is a major source of renewable electricity in the world. The industry is continuously searching for ways to improve the efficiency and reliability with which it produces energy. Here suggested a PID approach to turbine governor by utilizing human experience. The simulation model of Hydro Power Plant was constructed based on mathematical equations that summarize the behavior of the power plant. The simulation model of power plant is useful in stability studies. Simulation models are suitable for use in large scale system stability studies. The PID controller is designed and tested for three phases to ground fault by simulations which are reported in this paper. Results obtained by simulation show the rapidity and robustness of the PID controller. This controller is able to maintain the generated electrical power characteristics in spite of the changing user load.Â The invention and design of stabilized system means the ability of the system working with different load and fault.Â Controlling voltage system represent control an active power in electrical power grid by increasing and decreasing the generator voltage. In this paper completed models test that stability and flexibility of the Synchronized generator with over exciter, and under exciter by Governor and Excitation systems.Â Â Â